In sacco nutrient degradability of silage containing intact and defatted black soldier fly (Hermetia illucens) larvae - Mulianda, R.; Sofyan, A.; Herdian, H.; Laconi, E.B.; Ridla, M.; Wardani, W. W.; Jayanegara, A. (Journal of the Indonesian Tropical Animal Agriculture, 2021)
This study aimed to evaluate the in sacco nutrient degradability of total mixed ration (TMR) silage containing intact and defatted black soldier fly (BSF) larvae. The study evaluated four dietary treatments and six replications. The treatments consisted of control TMR silage without BSF larvae (R1), 20% intact BSF larvae + 80% TMR silage (R2), 20% chemically defatted BSF larvae + 80% TMR silage (R3), and 20% mechanically defatted BSF larvae + 80% TMR silage (R4). Samples were placed in polyester bags and incubated in the rumen in sacco up to 72 h. Nutrient degradability was evaluated for each time point interval. Results revealed that the lowest dry matter degradability (DMD) was found in R1 compared to all treatments (p < 0.05), while the highest DMD was found in R2 (p < 0.05). The highest organic matter degradability was found in R2 compared to R1, R3 and R4 (p < 0.05). Addition of BSF larvae to TMR silage increased the crude protein degradability (p < 0.05). In conclusion, inclusion of both intact and defatted BSF larvae into TMR silage did not have any adverse effects on nutrient profiles and showed a good nutrient degradation values in the rumen.